An evaluation of canal transportation and centering ability at different levels of root canals prepared by self-adjusting file using computed tomography (A comparative study) - Al-Gharrawi, Hikmet A; Abbas, Farah Salahalden (Journal of Baghdad College of Dentistry, 2014)
Background: The new concepts and technologies continue to change the dynamics of endodontic practices in the world. Rapid and significant changes in techniques, instrument design, and the type of metals used to manufacture endodontic instruments which have been made during the last few years in an attempt to overcome canal preparation errors. The purpose of this study is to measure and compare canal transportation and centering ability of Self Adjusting File with two rotary nickel-titanium (Ni-Ti) systems, ProTaper and BioRaCe at different levels. Material and Methods: Forty five distal roots of mandibular first molars with moderate curvature were selected using Schneider method. Roots were divided randomly into 3 groups of 15 each and were scanned using Computed Tomography (Initial scan). After canal preparation with ProTaper (group A), BioRaCe (group B), and Self Adjusting File (group C) the roots were rescanned (Final scan), the degree of canal transportation and centering ability were assessed at apical (4 mm), middle (6 mm), coronal (9 mm) sections using computed tomography. The collected data were statistically analyzed using ANOVA and Least Significant Difference tests. Results: There were no statistically significant differences among the groups at level 4 mm and level 9 mm (P ? 0.05). However, at level 6 mm there was a highly significant difference between (A) and (B) groups (P ? 0.01) and there was a significant difference between (A) and (C) groups (P ? 0.05). There were no statistically significant differences among different levels of (A) and (C) groups (P ? 0.05), while (B) group showed a highly significant difference between 4 mm and 9 mm levels and between 6 mm and 9 mm levels (P ? 0.01). Regarding canal centering ability, there was no statistically significant difference among the three groups at different levels (P ? 0.05)., while (B) group showed a significant difference between 4 mm and 9 mm levels (P ? 0.05), and a very highly significant difference between 6 mm and 9 mm levels (P ? 0.001). Conclusion: The study demonstrated that canal preparation with the three designs of Ni-Ti instruments produced canal transportation. Self Adjusting File group showed less canal transportation than ProTaper group. There was a comparable value of canal centering ability among different levels in each group except in BioRaCe group.